PUBLIC DOMAIN AS INDONESIA'S TRADEMARK LAW IN THE UTILITARIAN'S PERSPECTIVE - Trisa Rembonita; Fokky Fuad Wasitaatmaja (International Journal Multidisciplinary Science, 2024)
Indonesia’s Intellectual property rights encompass trademarks’ protection, copyrights, patents, geographical indications, industrial designs, circuit layout designs, and trade secrets, including aqua, the botol, and ecoprint, which use generic words and non-distinctiveness and disturb public order. Ecoprint became a public domain in 2001. However, it was approved as a trademark of products by the DGIPR in 2019 and protected by the law, allowing it to reap the economic benefits. The research problem is: How is the public domain of ecoprint used by trademarks being reviewed in positive Indonesian law from the perspective of utilitarian theory? The research uses a normative descriptive method with a conceptual approach and a comparative approach from secondary data, primary and secondary legal materials, and is analyzed using Jeremy Bentham's theory of utility, "the greatest happiness from the greatest number, namely through the provision of livelihood, abundance, security, and equality." The results indicate that Indonesian law does not explicitly manage the public domain as an intellectual property right that provides direct benefits to the community. The public domain becomes a trademark, creating incentives only for trademark owners instead of the community. IPR should cover the public domain to ensure incentives that benefit the wider welfare, including MSMEs.